MEMPERKENALKAN SEJARAH PAHLAWAN NASIONAL ZAENUL ARIFIN BAGI PESERTA DIDIK MI/SD DI INDONESIA - Mustainah, Hayati (STAINU Purworejo, 2020)
Merdeka is a word that has been eagerly awaited by the Indonesian people especially during the colonial period. Where the Indonesian people were completely colonized by the Netherlands, Japan, and England, even forced labor forced to seize all the spices and other natural resources in Indonesia. To the Japanese occupation masses, the Japanese emphasized and also urged the army of God (Hizbual Warriors) to give their independence to Japan, but the Hizbual Warriors immediately changed their minds and also formed new warriors. The new Laskar-laskar were taken by five santri from various boarding schools in Indonesia. The aim was to form new armies, so that the Hizbual army would become a powerful army of gods and be able to drive out invaders. The new Laskar-laskar will be trained first in the army in Cibarusah, West Java, led directly by KH.Zaenul Arifin, and the army will be led by KH.Hasyim asy’ari. Zainul arifin Is a native of the city of Nopan, North Sumatra then finished his HIS school in Jambi and then he migrated to Jakarta and worked under the auspices of the government. After that not long afterwards he was appointed as an Indonesian hero. And as for the values of principality in daily life.